Kata Serapan Makanan dan Minuman dari Bahasa Cina - Rahmawati, Assa (Paradigma: Jurnal Kajian Budaya, 2023)
The evidence of cultural link between Indonesia and China does not always could be seen from classical artefacts only but also from the existence of some vocabularies in the written and oral language in Indonesian language (Bahasa Indonesia). Survey concerned with the vocabularies in Indonesian language which derived from foreign language, including those words derived from Chinese language, was conducted by Russell Jones. The result had been written in a book called ‘Loan Words in Indonesian and Malay’. The survey had recorded around 1.100 words in Chinese language which had been borrowed by the Indonesian language and had spread out in differnt kinds of aspect of meaning, including the aspect of meaning related to food and beverage, which will be described in this paper. with Indonesian in the more penetrating globalization process in Asia in the 21st century. The research aims to examine the binding of two cultures tied in the knot in the marriage institution, its problem and negotiation. The qualitative methods used here is conducted through questionnaire and direct interview and through the social media. The result of which shows that factors such as cultural difference, respective country rules, and family tie interfere the social interaction in mixed marriage. But, despite the challenges, it is capable to generate negotiation and cultural appropriation of each party to support a multicultural and cosmopolitan marriage.